Observations of toroidal plasma rotation reversal in the Aditya-U tokamak. (9th September 2019) - Shukla, G.; Shah, K.; Chowdhuri, M.B.; Raj, H.; Macwan, T.; Manchanda, R.; Nagora, U.C.; Tanna, R.L.; Jadeja, K.A.; Patel, K.; Mayya, K.B.K.; Atrey, P.K.; et al.
Abstract: An impurity ion toroidal rotation profile has been observed in the ohmic discharges of the Aditya-U tokamak from the Doppler-shifted passive charge exchange line emission of C 5+ at 529 nm. The line has been monitored using a space-resolved visible spectroscopy diagnostic consisting of a 1 m multi-track spectrometer coupled with a charge coupled device (CCD) detector. In typical discharges with central chord-averaged electron density  ≲2.5  ×  10 19 m −3, the maximum toroidal rotation velocity at the plasma core is found to be  −20 km s −1 in the counter-current direction. Reversal of plasma toroidal rotation is observed for high electron density discharges with a central chord-averaged density of ~5  ×  10 19 m −3 . During the rotation reversal, the direction of toroidal rotation changes to the co-current direction in the core. Interestingly, in the discharges with a central chord-averaged electron density of  ≲2.5  ×  10 19 m −3, where neon gas is injected at the plasma current flat-top, the toroidal rotation reversal has been observed after the gas puff.